A milder form of molybdenum cofactor deficiency type A presenting as Leigh's syndrome-like phenotype highlighting the secondary mitochondrial dysfunction: a case report - Almudhry, Montaha; Prasad, Asuri N.; Rupar, C. Anthony; Tay, Keng Yeow; Ratko, Suzanne; Jenkins, Mary E.; Prasad, Chitra (Frontiers in Neurology, 2023)
Background: Molybdenum cofactor deficiency (MoCD) (OMIM# 252150) is an autosomal recessive disorder caused by mutations in four genes involved in the molybdenum cofactor (MOCO) biosynthesis pathway.We report a milder phenotype in a patient with MOCS1 gene mutation who presented with a Leigh-like presentation.We present the case of a 10-year-old boy who was symptomatic at the age of 5 months with sudden onset of dyskinesia, nystagmus, and extrapyramidal signs following febrile illness. Initial biochemical, radiological, and histopathological findings indicated a Leigh syndrome-like phenotype; however, whole-exome sequencing detected compound heterozygous mutations in the MOCS1 gene, c.1133 G>C and c.217C>T, confirming an underlying MoCD. This was biochemically supported by the low uric acid level of 80 (110−282 mmol/L), low cystine level of 0 (3-49), and a urine S-Sulfocysteine was high at 116 (0-15) mmol/mol creatinine. The patient was administered methionine-and cystine-free formulas. The patient has remained stable, with residual intellectual, speech, and motor sequelae.This presentation expands the phenotypic variability of late-onset MoCD A and highlights the role of secondary mitochondrial dysfunction in its pathogenesis.